2017
DOI: 10.1123/ijsnem.2016-0053
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Dehydration and Inadequate Nutritional Knowledge Among University and Club Level Athletes

Abstract: Although dehydration of ≥ 2% body weight (BW) loss significantly impairs endurance performance, dehydration remains prevalent among athletes and may be owing to a lack of knowledge in relation to fluid requirements. The aim of this study was to assess the hydration status of university/club level athletes (n = 430) from a range of sports/activities (army officer cadet training; bootcamp training; cycling; Gaelic Athletic Association camogie, football and hurling; golf; hockey; netball; rugby; running (sprintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
74
3
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(97 citation statements)
references
References 0 publications
9
74
3
2
Order By: Relevance
“…The loss of body mass with no water intake is associated with poor memory and attention [7]. Studies have reported dehydration by 1–2%, impairs cognitive performance and impacts psychomotor and memory skills [811]. Fluid deficit of 4% decreases performance, causes headaches, irritability, sleepiness and increases respiratory rate with increase in temperature among children [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of body mass with no water intake is associated with poor memory and attention [7]. Studies have reported dehydration by 1–2%, impairs cognitive performance and impacts psychomotor and memory skills [811]. Fluid deficit of 4% decreases performance, causes headaches, irritability, sleepiness and increases respiratory rate with increase in temperature among children [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, public awareness of dehydration is not widely assessed. The knowledge of dehydration is well documented among athletes [11, 1518]. According to a survey conducted among dieticians, 76% had knowledge for dehydration definition and 55% had knowledge for water intake recommendation [19].…”
Section: Introductionmentioning
confidence: 99%
“…13 In athletes, body weight loss >2% may impair performance and compromise function. 19,20 However, in a recent metaanalysis, Goulet 21 reported that reductions of up to 4% in body weight may not hinder endurance performance. A 10% decrease in body weight is a significant challenge, and although unlikely, in routine situations, was intentionally selected to provide direct evidence that systemic dehydration can change vocal fold tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Validations of methods to monitor hydration status and the development of an appropriate individualized hydration strategy should be well informed [15]. Another survey study also revealed a high rate of insufficient knowledge regarding dehydration and nutrition among university and club-level athletes [24]. BW could be a useful index for degree of dehydration, and the fluid deficit during exercise was recommended to be limited to less than 2% of BW [2].…”
Section: Discussionmentioning
confidence: 99%